Social support in neoplastic disease - Fopka-Kowalczyk, Małgorzata (Psychoonkologia, 2013)
The diagnosis of the chronic disease causes the change in every aspect of human functioning. It especially happens in the case of neoplastic disease. This is the experience that influences the mode of current living. It seems that the change appears in four basic dimensions of human life: somatic, social, emotional and spiritual. All of them necessitate the search for new solutions and actions. We need to underline that the presence of disease affects the sick person as well as their relatives. Undoubtedly, the situation of the disease and changes it causes in the patient’s life requires the search for special support during that period. It is often expected from the relatives, with whom the sick person gets on well. It concerns the search for “the net of support”: relatives, friends or professionals, when the help of the family is not sufficient. Received care may be different in respect of its content. Among the kinds of social support in neoplastic disease the most important appears to be emotional and evaluative assistance which enables the sick to preserve high self-esteem and helps them in dealing with a disease. A crucial element of social support in neoplastic disease is also broadly defined psychological education on the very disease, its treatment, and possible accompanying symptoms. It may also be helpful in work with emotions, views on disease, as well as in finding internal personal resources to deal with future problems.